Modulating effects of mycotoxin and oxidized oil on intestinal microbiota in broiler chickens - Kouassi R. Kpodo; Daniel J. Milliken; Philip M. Campos; Monika Proszkowiec‑Weglarz; Merlin D. Lindemann; Sunday A. Adedokun (PLoS ONE, 2025)
Climatic change and increased use of alternative sources of feed ingredients could influence poultry production. Mycotoxin and oxidized oil are two contaminations that may occur in chicken feed as a result of climate change and use of alternative feed ingredients, and these factors may have differential and potentially additive effects on birds’ intestinal microbiota. The study objective was to determine the main effects of corn, oil quality, and their interaction on ileal content, ileal scrapings, cecal content, and whole cecum (content and tissue) microbiota in broiler chickens. Broiler chickens were raised for 21 days post-hatch and fed diet made with regular or mycotoxin-contaminated corn (7,959 ppb of deoxynivalenol, 2.1 ppm of aflatoxin, 23,200 ppb of fumonisin, and 1,403 ppb of zearalenone), and regular or oxidized (148 meq/kg) oil. Bacterial genomic DNA was extracted and sequenced targeting the variable (V3-V4) region of the 16S gene. The bioinformatic and statistical analysis of the microbiota data showed mycotoxin and mycotoxin by oxidized oil interaction increased the richness and evenness in the ileal content and only evenness in the cecal content. Mycotoxin and mycotoxin by oxidized oil interaction also increased beta diversity based on the variability in microbial community in the ileal content while increasing the abundance of bacterial taxa, including Streptomyces and Escherichia-Shigella, and predicted pathways related to RNA and DNA synthesis (Mycothiol and pyrimidine deoxyribonucleotides synthesis) and redox regulation (ergothioneine biosynthesis) in ileal content and pathways related to glycol metabolism and degradation and amino acids degradation were increased in the cecal content. Streptomyces has been associated with mycotoxin detoxication, and its increase could reduce the negative effects of mycotoxins contrary to Escherichia-Shigella, which has been negatively correlated with weight gain in chickens. These results show that mycotoxin alone and its combination with oxidized oil affect bacterial diversity and abundance mostly in the ileum content and predicted metabolic pathways across intestinal sections.